Interleukin-17A Interweaves the Skeletal and Immune Systems - Tang, Mengjia; Lu, Lingyun; Yu, Xijie (Frontiers in Immunology, 2021)
The complex crosstalk between the immune and the skeletal systems plays an indispensable role in the maintenance of skeletal homeostasis. Various cytokines are involved, including interleukin (IL)-17A. A variety of immune and inflammatory cells produces IL-17A, especially Th17 cells, a subtype of CD4+ T cells. IL-17A orchestrates diverse inflammatory and immune processes. IL-17A induces direct and indirect effects on osteoclasts. The dual role of IL-17A on osteoclasts partly depends on its concentrations and interactions with other factors. Interestingly, IL-17A exerts a dual role in osteoblasts in vitro. IL-17A is a bone-destroying cytokine in numerous immune-mediated bone diseases including postmenopausal osteoporosis (PMOP), rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondylarthritis (axSpA). This review will summarize and discuss the pathophysiological roles of IL-17A on the skeletal system and its potential strategies for application in immune-mediated bone diseases.